Determining the Optimal Season for Detection of Prune Dwarf Virus and Prunus Necrotic Ringspot Virus in Sour Cherry Cultivars - Pavliuk, Liliia; Udovychenko, Kateryna; Riaba, Iryna; Bublyk, Mykola (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The aim of this study was to select the optimal season and tissues of cherry plants for detection of prune dwarf virus (PDV) and prunus necrotic ringspot virus (PNRV) in climatic condition of Ukraine. The experiment was performed by DAS-ELISA using certified test kits manufactured by Loewe Biochemica GmbH (Germany). Each sample was tested twice. The plates were incubated at room temperature and the results were recorded after 60 minutes. Trees of cherry varieties ‘Bohuslavka’ (PDV infected) and ‘Kseniia’ (PNRV infected) were selected for testing. Healthy plants of the same varieties were selected as the negative controls. The highest absorbance levels of PDV and PNRV were recorded at the beginning of the growing season. Young leaves and flowers were the most reliable source for detection of these viruses. Instead, in October there was high possibility of falsenegative results